Flux gourmet [videorecording (DVD)] - Strickland, Peter, 1973-; Butterfield, Asa, 1997-; Christie, Gwendoline, 1978-; Labed, Ariane; Mohamed, Fatma, 1975-; Papadimitriou, Makis, 1975-; Bremmer, Richard; Bill, Leo (IFC Midnight, 2022)
At an institute devoted to culinary and alimentary performances, a dysfunctional sonic collective faces power struggles, vendettas, and gastrointestinal disorders.